Artificial Intelligence-Supported English Language Instruction: Impacts on Student Achievement - Dja'far, Veri Hardinansyah; Agustina, Lia; Hamidah, Fitria Nur (Eduvelop: Journal of English Education and Development, 2025)
In the continuously evolving digital era, mastering English in a professional context has become a primary necessity, especially for accounting students who are required to understand technical terminology and effectively communicate financial information. This research aims to explore the effectiveness of artificial intelligence tools in enhancing the teaching of English for Accounting, specifically within the framework of English for Specific Purposes education. Utilizing a quasi-experimental design, the study incorporates a pretest and posttest control group, comprising two distinct groups of accounting students. One group receives conventional instruction, while the other benefits from AI-enhanced teaching methods. The findings suggest that the group that participated in the experiment showed notable enhancements in their knowledge of technical terms, ability to comprehend financial documents, and proficiency in both writing and communication related to accounting when compared to the group that did not participate. Additionally, the use of AI proved to help reduce cognitive load and enhance learning motivation among students. These findings imply the need for systematic integration of artificial intelligence technology into the ESP curriculum, as well as training for instructors to optimize its use. Thus, AI technology plays not only a supportive role but also serves as an adaptive learning strategy relevant to current industry needs.